The Effect Of Self-Efficacy And Self-Regulated Learning On Student Academic Procrastination - Fahmi Khafif, Muhammad; Fraick Nicky Gillian Ratumbuysang, Monry; Hasanah Baseran Nor, Mahmudah (Manager : Jurnal Ilmu Manajemen, 2023)
Students as part of educational institutions are required to be able to develop various potentials optimally. In reality, students often face their assignments and appear reluctant and delay doing them. This study aims to seek dominance the effect of self-efficacy and self-regulated learning on academic procrastination. The type of research used associative quantitative research, research that asks the relationship between 2 or more variables. this study used a causal relationship. the population in this study totaled 215 from the 2018, 2019 and 2020 class. the sample in this study totaled 140 which were collected using random sampling. The results showed that there was a significant negative effect of self-regulated learning on academic procrastination with the result tcount > ttable (13.391> 1.977), there was no significant negative effect of self-regulated learning on student academic procrastination with the results tcount < ttable (1.606< 1.977), there is a simultaneous effect of self-efficacy and self-regulated learning on student academic procrastination with the results Fcount>Ftable (239.889>3.08) and obtained R2 (R Square) of 0.778 or 77.8% while the remaining 23.8 % is influenced by other variables not tested in this study. The number of respondents is not as much as expected and researchers experienced difficulties when distributing questionnaires to respondents. This study examines student academic procrastination to determine the causation of partial and simultaneous self-efficacy and self-regulated learning